Murcha bacteriana do eucalipto: dinâmica espaço-temporal e resistência de clones em campo - Rossi, Ana Paula (2021)
The expansion of eucalyptus cultivation has favored the occurrence of diseases, and consequently the reduction of productivity causing economic losses. Among the diseases, the bacterial wilt caused by Ralstonia solanacearum, one of the most destructive pathogens in the world due to its global distribution and genetic variation, stands out. Given the importance of this pathogen, and the scarcity of studies on the epidemiology of bacterial wilt in eucalyptus plantations, this study aimed to understand the spatio-temporal dynamics of bacterial wilt and evaluate the resistance of clones in the field. The experiment was conducted in a commercial plantation in state of Maranhão, using the eucalypt clone FGCA0385, species Eucalyptus urophylla var. platyphylla. The spatial dynamics of the disease was performed by determining the Index of Dispersion (ID), the Modified Taylor’s Law (MTL) and the Dynamics and Structure Analysis of the Foci (DSAF). For temporal dynamics the disease incidence progress curve was plotted, and the data were analyzed by simple linear regression analysis, fitted to three empirical models, Logistic, Monomolecular and Gompertz. The experiment on clone resistance to eucalyptus bacterial wilt was conducted under commercial planting conditions in state of Pará, using 308 clones, composed of 05 species and 22 hybrids, with seedlings from the states of SP, BA, and MA. To analyze the resistance of eucalyptus clones to eucalyptus bacterial wilt, we used the procedure of variance estimation and prediction of genetic values (REML/BLUP) to the data of the variable area under the disease progress curve (AUDPC) calculated by the trapezoidal integration method, with the aid of the Computerized Genetic Selection program - SELEGEN - REML/BLUP. There was an aggregation pattern for plants symptomatic of eucalyptus bacterial wilt verified by Modified Taylor's Law. As for the analysis of the Dynamics and Structure Analysis of the Foci (DSAF), 69 foci of the disease occurred, 44 of which were unitary, and the average number of plants per foci was 1.63. The foci are longer in the direction of the planting line and were characterized as not compacted. The epidemics were best described by the Monomolecular model, from which an incidence of 48.98% was estimated in the seventh year of the study. Regarding the resistance of clones to eucalyptus bacterial wilt in the field, it was found that all 05 species and 22 eucalyptus hybrids evaluated in the experiment are susceptible to bacterial wilt and that of the 308 clones, only 25 show vertical resistance.